Multiple Periods Destroy the Axiomatic Base of Expected Utility Theory and its Standard Generalisations - Robin Pope (University of Bonn, Bonn Graduate School of Economics (BGSE), 2006)
It is here shown that the extension of expected utility theory to multiple periods destroys the axiomatic base by introducing timing contradictions in what the chooser knows at a single time point. It is shown that some of these timing contradictions remain even if, as Samuelson (1952) proposed, no segment of the outcome space (to which utility attaches) commences before all risk is passed.
Keywords: D90; D81; 330; expected utility theory; rank dependent theories; axioms; single period; multiple period; timing contradictions; degree of knowledge ahead